Thresholds for storm impacts on an exposed sandy coastal area in southern Portugal - Almeida, L. P. (2018)
Storms are one of the most important phenomena responsible for coastal erosion. Their destructive power presents major challenges for coastal management, and knowledge of their characteristics and associated consequences is therefore of paramount importance. In this study, thresholds for storm impacts are defined for a sandy coast in southern Portugal (Faro beach, Ria Formosa) using two different approaches: i) hydrodynamic conditions associated with historical storm impacts (i.e., infrastructural damage); and (ii) computed maximum wave run-up values (RHIGH) compared with beach morphology. Damage thresholds are defined as limits above which the action of a storm exceeds beach front response capability and starts to act directly on human infrastructures. According to method (i), four different thresholds were defined. For individual storms directed from the SW the threshold is a significant wave height of 4.7 m with a storm duration of 2 days, and for storms directed from the SE is a significant wave height of 6 m with a storm duration of at least 2 days. Regarding storm groups, for those directed from the SW the threshold is 2 storms lasting at least 2 days each with significant wave heights greater than 3.5 m, whilst for those directed from the SE the threshold is 3 short storms (lasting 1 day each) with significant wave height over 3.9 m. The return period for the SW storm group threshold is just 1.7 years. For method (ii), beach morphological parameters (DHIGH — highest elevation of the frontal dune; DLOW — elevation of the dune base; and tanβf — foreshore slope) were determined for five chosen cross-shore profiles along the study area, and RHIGH computed for different hydrodynamic conditions. Results were validated through field observations of storm impacts. The lowest thresholds for overwash are along the central part of the study area where a dune crest is absent due to human occupation. The highest thresholds for overwash are on those profiles where a frontal dune is well developed or a foredune ridge is present (western and eastern parts of the study area). This study presents a methodological strategy to compute realistic thresholds for storm impacts along Faro beach based on historical datasets of hydrodynamics and storm impacts information. The approach could be implemented in other coastal areas to provide a comprehensive assessment of the storm impact, requiring only simple information like offshore storm hydrodynamics characteristics, beach morphology and reports of coastal infrastructure damage.